PsycEXTRA Dataset 2008
DOI: 10.1037/e621222011-001
|View full text |Cite
|
Sign up to set email alerts
|

Driver Behavior at Highway-Railroad Grade Crossings: A Literature Review from 1990-2006

Abstract: This document is disseminated under the sponsorship of the Department of Transportation in the interest of information exchange. The United States Government assumes no liability for its contents or use thereof. Notice The United States Government does not endorse products or manufacturers. Trade or manufacturers' names appear herein solely because they are considered essential to the objective of this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…1a) and passive (stop sign, see Fig. 1b) warning systems (Yeh & Multer, 2008). The current safety approach to reducing RLX crashes focuses on countermeasures either on the approaching road or at the crossing itself, through the use of signs, warning sounds, pavement markings, flashing lights and boom gates.…”
Section: Introductionmentioning
confidence: 99%
“…1a) and passive (stop sign, see Fig. 1b) warning systems (Yeh & Multer, 2008). The current safety approach to reducing RLX crashes focuses on countermeasures either on the approaching road or at the crossing itself, through the use of signs, warning sounds, pavement markings, flashing lights and boom gates.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it was the least sensitive, but at these crossings, drivers made the most risky decisions. The use of a stop sign at grade crossings is controversial; the similarities between a driver's decision at a grade crossing and that at a highway intersection initially prompted interest in its use, but the results of several observational studies have reported low rates of compliance (see Yeh and Multer, 2008). In fact, the estimate of β for 1986 was 8.24, reflecting an inclination to proceed at stop signprotected crossings.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of warning times on driver compliance and means to increase the credibility of warnings provided by level crossing systems have been discussed in a literature review by Yeh and Multer [27]. According to a field study [28] mentioned by Yeh and Multer [27], most violations occurred when the warning time was more than 50 s. At level crossings equipped with flashing lights but not gates, violations increased when the warning time exceeded 35 s. It can also be argued that a shorter warning time would better reflect the requirements of end users.…”
Section: Modelling Of the Systemmentioning
confidence: 99%
“…The impact of warning times on driver compliance and means to increase the credibility of warnings provided by level crossing systems have been discussed in a literature review by Yeh and Multer [27]. According to a field study [28] mentioned by Yeh and Multer [27], most violations occurred when the warning time was more than 50 s. At level crossings equipped with flashing lights but not gates, violations increased when the warning time exceeded 35 s. It can also be argued that a shorter warning time would better reflect the requirements of end users. However, it can also be argued that the system will increase the awareness and alertness of the driver and provide useful information to him/her even in cases where the driver decides not to wait for the train to pass first, and that the driver is not necessarily expected to wait at the level crossing every time he/she receives a warning.…”
Section: Modelling Of the Systemmentioning
confidence: 99%